2004
DOI: 10.1007/s00586-003-0559-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric seatbelt injuries: unusual Chance's fracture associated with intra-abdominal lesions in a child

Abstract: The authors report the case of a 7-year-old child involved in a motor vehicle accident. She sustained an unusual flexion-distraction vertebral injury. This spinal injury was related to seatbelt use and was associated with intra-abdominal lesions. The spinal lesion consisted of a posterior ligamentous disruption with widening of the posterior intervertebral space at two adjacent lumbar levels. The purpose of this case report is to describe an atypical and perhaps often unrecognized spinal lesion and to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In addition, the use of MRI in flexion distraction fractures has rarely been reported. Ceroni et al 12 There are great differences in the anatomy of adult and children due to the presence of growth structures and more elastic soft tissues. In children, the disc can be deformed more significantly than in adults due to a high water content in the nucleus pulposus and a more elastic collagen fiber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of MRI in flexion distraction fractures has rarely been reported. Ceroni et al 12 There are great differences in the anatomy of adult and children due to the presence of growth structures and more elastic soft tissues. In children, the disc can be deformed more significantly than in adults due to a high water content in the nucleus pulposus and a more elastic collagen fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are case reports [11][12][13][14][15][16][17][18] or short series. 6,10,19 -21 To our knowledge, the present study represents the largest series of children with flexion distraction fracture in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11 Published reports on the management of pediatric Chance fractures consist of case reports and small patient series. 1,4,7,14 The original treatment recommended by Chance was reduction in hyperextension and immobilization in a cast. Most investigators have reported good results using such conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, 1 had a sample size greater than 20 patients, 7 four had between 10 and 20 patients, 4,[8][9][10] five had between 4 and 9 patients, 1,5,11-13 and 15 were case series or case reports with 3 or fewer patients. 3,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Demographic Data. Patient age was available for 115 patients in these studies and ranged from 2 to 17 years.…”
Section: Study Characteristicsmentioning
confidence: 99%